Determinants of Corporate Performance in One of Indonesia's Foreign Banks - Dedi Nurfalaq; Michael Christian (Dinasti International Journal of Education Management And Social Science, 2024)
This research aims to assess the impact of organizational learning and leadership style on corporate performance (CP), with organizational culture acting as a moderator. The study was carried out at an Indonesian bank that is owned by the South Korean government. Therefore, this research will examine the impact of South Korean business culture, which is unfamiliar territory. This study employs a quantitative methodology. The findings of this study demonstrate that organizational learning significantly impacts business performance. Moreover, the leadership style also has an impact on the overall functioning of the company. Similar outcomes are also demonstrated in the case of organizational culture, which has an impact on corporate performance. Organizational culture plays a role in influencing organizational learning and corporate performance. Organizational culture does not have a moderating effect on the relationship between leadership style and business performance, as evidenced by many findings.